2021
DOI: 10.1098/rsif.2021.0264
|View full text |Cite
|
Sign up to set email alerts
|

Seismic localization of elephant rumbles as a monitoring approach

Abstract: African elephants ( Loxodonta africana ) are sentient and intelligent animals that use a variety of vocalizations to greet, warn or communicate with each other. Their low-frequency rumbles propagate through the air as well as through the ground and the physical properties of both media cause differences in frequency filtering and propagation distances of the respective wave. However, it is not well understood how each mode contributes to the animals’ abilities to detect these rumbles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…163 More recent studies have identified the social and environmental monitoring purposes associated with this communication channel in elephants. [164][165][166] Anti-predatory structures and strategies It is thought that the origin of many distinctive morphological and/or behavioral traits of living organisms is related to the selective pressure exerted by for the multipletarget illusion. An enlarged echo illusion would likely lead bats to target the hindwing just behind the abdomen of the moth, at the perceived echo center (highlighted in green); however, bats targeted this region only 25% of the time (adapted from Rubin et al 171 ).…”
Section: Scorpion Sensingmentioning
confidence: 99%
“…163 More recent studies have identified the social and environmental monitoring purposes associated with this communication channel in elephants. [164][165][166] Anti-predatory structures and strategies It is thought that the origin of many distinctive morphological and/or behavioral traits of living organisms is related to the selective pressure exerted by for the multipletarget illusion. An enlarged echo illusion would likely lead bats to target the hindwing just behind the abdomen of the moth, at the perceived echo center (highlighted in green); however, bats targeted this region only 25% of the time (adapted from Rubin et al 171 ).…”
Section: Scorpion Sensingmentioning
confidence: 99%
“…Note that seismic rumble signals do not contain as many harmonics as seen in acoustic signals, presumably due to their coupling characteristics to the ground Reinwald et al. (2021); this will need to be investigated in a future study. However, it is important to note that the lowest seismic frequency of the rumble is the most interesting and useful one, as that signal will propagate furthest.…”
Section: Resultsmentioning
confidence: 97%
“…The rumbles detected in the seismic data were also validated by their presence in the microphone data. The spectrograms were processed differently than in the previous section (see supplementary material for details), and following Reinwald et al (2021), we applied the structure tensor (Harris & Stephens, 1988) of the spectrogram as a filter. This approach enhances the rumbles which contain sharp contours along the frequency axis, and diminishes the broadband locomotion signals, as can be seen in Supplementary Figures S2 and S3.…”
Section: Locomotion Versus Vocalisationmentioning
confidence: 99%
“…Seismology is a well-established discipline (e.g., Lecocq et al, 2020) and therefore it is not surprising that it has already provided the first applications of ecotremology in monitoring elephants either by vibrational component of their infra-sound vocalizations or by incidental vibrations induced by locomotion (Wood et al, 2005;Mortimer et al, 2018;Parihar et al, 2021;Reinwald et al, 2021). The latter approach also allows differentiating between large mammal species (Wood et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…While affordable seismic sensors such us geophones are available (e.g., Reinwald et al, 2021), recording from substrates like plants requires a different recording approach. Portable laser vibrometers are the most sensitive and avoid the problem of mass loading, but are costly and complex.…”
Section: Spatial and Temporal Variation In Vibroscapementioning
confidence: 99%